2019
DOI: 10.1158/1078-0432.ccr-19-1106
|View full text |Cite
|
Sign up to set email alerts
|

ImmunoPET, [64Cu]Cu-DOTA-Anti-CD33 PET-CT, Imaging of an AML Xenograft Model

Abstract: Purpose: Acute myeloid leukemia (AML) is a highly aggressive form of leukemia, which results in poor survival outcomes. Currently, diagnosis and prognosis are based on invasive single-point bone marrow biopsies (iliac crest). There is currently no AML-specific noninvasive imaging method to detect disease, including in extramedullary organs, representing an unmet clinical need. About 85% to 90% of human myeloid leukemia cells express CD33 cell surface receptors, highlighting CD33 as an ideal candidate for AML i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Therefore, the GVHD mouse model in allogeneic BMT settings using TMI would enable us to further understand the role of radiation-induced gut damage in GVHD. (iv) A recent study using an anti-CD33-PET imaging modality showed that AML disease localizes mostly in the skeletal system and is highly heterogeneous (41). The PET-guided functional TMI (fTMI) could allow localized radiation boosts to sites of high disease burden to enhance increased tumor cell killing without damaging the entire skeletal system(11,42).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the GVHD mouse model in allogeneic BMT settings using TMI would enable us to further understand the role of radiation-induced gut damage in GVHD. (iv) A recent study using an anti-CD33-PET imaging modality showed that AML disease localizes mostly in the skeletal system and is highly heterogeneous (41). The PET-guided functional TMI (fTMI) could allow localized radiation boosts to sites of high disease burden to enhance increased tumor cell killing without damaging the entire skeletal system(11,42).…”
Section: Discussionmentioning
confidence: 99%
“…In two recent studies, researchers reported the feasibility and satisfactory treatment efficacy of 90 Y-rituximab in patients with relapsed or refractory NHL. , Furthermore, several preclinical and clinical studies have reported the superior effectiveness of pRIT or RIT in treating lymphomas by targeting several targets, such as CD20, , CD38, and CD45 . CD33 is another alternative target for RIT of hematological malignancies , and for immunoPET imaging . Continuous innovation of the pRIT systems and incorporation of immunoPET techniques may reinvigorate the enthusiasm for managing hematologic malignancies with nuclear medicine approaches.…”
Section: Immunopet Imaging-guided Advanced Therapeuticsmentioning
confidence: 99%
“…913 CD33 is another alternative target for RIT of hematological malignancies 914,915 and for immunoPET imaging. 916 Continuous innovation of the pRIT systems and incorporation of immunoPET techniques may reinvigorate the enthusiasm for managing hematologic malignancies with nuclear medicine approaches. Readers are recommended to refer to an excellent review parsing RIT for more information.…”
Section: Immunopet Imaging-guided Advanced Therapeuticsmentioning
confidence: 99%
“…PDCs with a toxic payload attached, DM4 in the case of CX-2009, aim at delivering selectively their payload to tumors via widely expressed antigens, such as CD166. We evaluated the potential of CX-2009 by performing 89 Zr-immuno-PET and biodistribution studies in a CD166-positive H292 lung cancer mouse model in comparison with its radiolabeled benchmark compounds, the Probody therapeutic without DM4 (CX-191), the unmasked antibody drug conjugate (ADC) CX-1031, and the parental mAb CX-090 at three different doses (10,110, or 510 µg) and different time points (24,72, and 168 hours post-injection (p.i.)). Tumor uptake was similar for all constructs at 72 hrs p.i.…”
Section: Discussionmentioning
confidence: 99%
“…the different experimental groups, being 264 ± 145 mm 3 . As a first step, the biodistribution of [89 Zr]Zr-CX-2009 was assessed as a function of dose (10, 110, or 510 µg; Figure3Aand TableS1) and time(24,72, and 168 h p.i. ; Figure3Band TableS2).…”
mentioning
confidence: 99%